Pengaruh Model Pembelajaran Terhadap Tingkat Keterampilan Kolaborasi dan Kepemimpinan Siswa Kelas X Pada Materi Virus - sarisawati Intishar; Erna Wijayanti; Nur Khasanah (Undiksha, 2023)
The world of education has many ways for students to absorb various kinds of knowledge. Methods, tools and materials in learning are all included in the learning model. Learning models in the world of education are very varied. However, the learning model focuses more on students' understanding of the subject matter. Even though in the 21st century students are more demanded to have soft skills and hard skills. One of the soft skills needed is student skills in collaborating and leading. For this reason, the purpose of this study was to determine the influence of learning models on the level of collaboration and leadership skills of students. In this study, the model used was Collaborative Discovery Learning based on I-SETS for the experimental class and Discovery Learning for the control class. The results of this study found that I-SETS-based CDL learning can improve students' collaboration and leadership skills. I-SETS-based CDL when compared to discovery learning proved that there was a significant increase of 0.031 <0.05 with a t-count of 2,197 > 1,667 in collaboration skills. For leadership skills there is an increased significance of 0.048 <0.05 with a t-count of 2.015 > 1.667 t-table. This is like previous research that SETS-based discovery learning can improve students' collaboration skills.